Targeting CaN/NFAT in Alzheimer’s brain degeneration - Mackiewicz, Joanna; Lisek, Malwina; Boczek, Tomasz (Frontiers in Immunology, 2023)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by a progressive loss of cognitive functions. While the exact causes of this debilitating disorder remain elusive, numerous investigations have characterized its two core pathologies: the presence of β-amyloid plaques and tau tangles. Additionally, multiple studies of postmortem brain tissue, as well as results from AD preclinical models, have consistently demonstrated the presence of a sustained inflammatory response. As the persistent immune response is associated with neurodegeneration, it became clear that it may also exacerbate other AD pathologies, providing a link between the initial deposition of β-amyloid plaques and the later development of neurofibrillary tangles. Initially discovered in T cells, the nuclear factor of activated T-cells (NFAT) is one of the main transcription factors driving the expression of inflammatory genes and thus regulating immune responses. NFAT-dependent production of inflammatory mediators is controlled by Ca2+-dependent protein phosphatase calcineurin (CaN), which dephosphorylates NFAT and promotes its transcriptional activity. A substantial body of evidence has demonstrated that aberrant CaN/NFAT signaling is linked to several pathologies observed in AD, including neuronal apoptosis, synaptic deficits, and glia activation. In view of this, the role of NFAT isoforms in AD has been linked to disease progression at different stages, some of which are paralleled to diminished cognitive status. The use of classical inhibitors of CaN/NFAT signaling, such as tacrolimus or cyclosporine, or adeno-associated viruses to specifically inhibit astrocytic NFAT activation, has alleviated some symptoms of AD by diminishing β-amyloid neurotoxicity and neuroinflammation. In this article, we discuss the recent findings related to the contribution of CaN/NFAT signaling to the progression of AD and highlight the possible benefits of targeting this pathway in AD treatment.